PENGARUH PERSEPSI KUALITAS DAN MOTIVASI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MIE GACOAN, BALI - Fransisca Ivencita Teesen; Romulo Sinabutar (Jurnal Ekonomis, 2021)
This study aims to describe and analyze perceptions of quality and consumer motivation towards purchasing decisions. This research is a quantitative descriptive type using non-probability sampling with purposive sampling technique with the number of respondents 30 consumers who have consumed Mie Gacoan products. Hypothesis testing in this study uses multiple linear analysis which includes multiple regression analysis, T test, F test and the coefficient of determination. The measuring tool used is an online questionnaire using Google Form. The t test results on the perceived quality variable on purchasing decisions are (5.097> 2.052). From these results there is a partial influence between the perceived quality variable and the purchase decision. The consumer motivation variable does not have a partial effect on purchasing decisions. This is supported by the t test of 0.478 <2.052. The f test on the perceived quality variable and consumer motivation towards purchasing decisions is 20.816> 3.35. From these results it is known that each variable X has a simultaneous effect on variable Y.